2000
DOI: 10.1007/s003300050978
|View full text |Cite
|
Sign up to set email alerts
|

MR diagnosis of a congenital abnormality of the thoracic aorta with an aneurysm of the right subclavian artery presenting as a Horner's syndrome in an adult

Abstract: Congenital abnormality of the aortic arch is a diagnosis made most of the time incidentally in childhood, unless dysphagia or respiratory disorders occur before. A case of a complex aortic arch anomaly with an aneurysm of the right subclavian artery presenting as an isolated Horner's syndrome in an adult is reported herein. Magnetic resonance imaging led to this very unusual diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Other causes of second-order neuron Horner syndrome include neck or upper thoracic surgery; primary spinal nerve root tumors and lesions that compress the nerve roots, such as nerve root tumors or osteophytes; jugular venous ectasia; subclavian artery aneurysm; and other neck masses causing compression of the cervical sympathetic chain [22][23][24][25].…”
Section: Second-order Neuronsmentioning
confidence: 99%
“…Other causes of second-order neuron Horner syndrome include neck or upper thoracic surgery; primary spinal nerve root tumors and lesions that compress the nerve roots, such as nerve root tumors or osteophytes; jugular venous ectasia; subclavian artery aneurysm; and other neck masses causing compression of the cervical sympathetic chain [22][23][24][25].…”
Section: Second-order Neuronsmentioning
confidence: 99%
“…4,5 Anderson et al reported that 69% of patients who were found to have mycotic aneurysm were not known to have aortic coarctation prior to the onset of the infection, 1 highlighting the difficulty of this diagnostic challenge. Our patient is unique for multiple reasons, he had Streptococcus pneumoniae causing myostitis, 6 which has been reported but is uncommon, he had a unique early manifestation of the aneurysm, in the form of Horner's syndrome, 7,8 and he is the first reported case, to our knowledge, of this bacteria causing a mycotic aortic aneurysm.…”
Section: Discussionmentioning
confidence: 79%
“…Our patient is unique for multiple reasons, he had Streptococcus pneumoniae causing myostitis, 6 which has been reported but is uncommon, he had a unique early manifestation of the aneurysm, in the form of Horner's syndrome, 7,8 and he is the first reported case, to our knowledge, of this bacteria causing a mycotic aortic aneurysm.…”
Section: Discussionmentioning
confidence: 79%
“…There are numerous imaging approaches in the preoperative stage and also in the postoperative follow-up of patients with aortic coarctation. For anatomic assessment of the coarctation site and identification of collaterals, non-invasive magnetic resonance imaging/angiography and also CT angiography show an equal sensitivity to invasive catheter angiography and thus are widely used as follow up tool [26,27,28,29]; however for functional assessment, the estimation of pressure gradients across the (re)stenosis by direct catheter measurement or with the use of Doppler echocardiography remains mandatory. There is very few experience with the use of VEC-MR in coarctation patients [8,30,31,32].…”
Section: Discussionmentioning
confidence: 99%